A Critical Investigation of Parental Stress Management in Raising a Child With Cerebral Palsy at the Community-Based Rehabilitation Alliance - Michelle Amanda Kabageni (Uganda christian University, 2024)
This dissertation explored the difficulties of parental stress management when raising a child with cerebral palsy, looking at the experiences of parents within the Community Based Rehabilitation Alliance, Kiwanga, Uganda. The research was aimed to look deeper into the specific factors that contribute to stress among parents and the coping mechanisms that the parents used. Utilized a qualitative case study design while integrating integrating one on one interviews and questionnaires to gather exhaustive data from articipants. The findings showed that parents experienced a lot of stress which blocked their capability to cope effectively.One of the things that were identified as helpful were support groups. The study concluded while improvements on attitudes and support systems, there are still challenges that require further research into effective intervention mechanisms and long term health of parents. These findings underscore the relevance of developing complete support programs that address needs of parents raising children with cerebral palsy, alternatively contributing to better family wellbeing and adaptation